Avaliação do grau de definição dos projetos de emprendimentos de incorporação imobiliária: um estudo de caso - Joao Felipe Martins Abdala (2015)
Real estate companies are improving their design process. It becomes important to evaluate the maturity level of the design process. In this context, this research work aims presenting an exploratory study to evaluate the level of development and maturity of the design process in construction companies and real estate developers. This assessment was performed using the Project Definition Rating Index (PDRI),developed by the Construction Industry Institute. It is also pointed out a critical analysis of the applicability of the tool in real estate projects.The research was carried out through exploratory case study, mapping the company design process, and implementing the PDRI. Evidence sources embraced interviews with managing partners and designers,design analysis, minutes of meetings, management reports and other sources. The results point to the fact that the PDRI is appropriate to assess the level of maturity of the design process, but in the case of projects with established typology, a simplification is suggested. Moreover, it is highlighted that critical steps in the design process are neglected in building construction design processes. In the case studies the PDRI is adequate to indicate deficiencies in the design process. The analysis indicates that some elements need to be further developed.Especially the compatibility of project activities and consideration of performance issues.